Hofmannsthal and “die göttliche Briehl” (Studia austriaca, 2013)
This article highlights the hitherto neglected significance of the small market town, and erstwhile spa resort, of Hinterbrühl in Lower Austria to Hugo von Hofmannsthal’s life and work. This discussion is set in a cultural-historical context of Hinterbrühl’s function as a place of encounter in the golden age of the spa resort. The article traces the lasting influence of Hinterbrühl in Hofmannsthal’s oeuvre, whether this be through the people he met there, as evidenced by the fragment Silvia im “Stern”, or in the sublimation of the Lower Austrian landscape in the enigmatic Das Märchen der 672. Nacht.